Correlation between serum sortilin levels and severity of extracranial carotid artery stenosis. Issue 11 (20th August 2021) - Simsek, Zeki; Alizade, Elnur; Güner, Ahmet; Zehir, Regayip
Abstract: Objective: Atherosclerosis is a chronic inflammatory vascular condition characterised by intimal thickening with cholesterol accumulation and macrophage foam cell infiltration causing plaque formation at the site of the injured vessel wall. This condition is a major contributor to carotid artery stenosis (CAS). Sortilin, a member of the mammalian vacuolar protein sorting 10 protein family, promotes uptake of low‐density lipoprotein particles into macrophages with consequent foam cell formation independent of the low‐density lipoprotein receptor, and thereby, accelerates atherosclerotic plaque formation and progression. We investigated the correlation between serum sortilin levels and the severity of extracranial CAS. Materials and Methods: The study included 149 patients who underwent carotid angiography for suspected carotid artery disease. The North American Symptomatic Carotid Endarterectomy Trial 2011 criteria were used to determine the degree of CAS. Serum sortilin concentrations were measured using the enzyme‐linked immunosorbent assay. Results: Serum sortilin levels were significantly higher in the severe CAS than in the non‐severe CAS group (2.71 ± 0.71 ng/mL vs 1.63 ± 0.57 ng/mL, P < .001). Receiver operating characteristic curve analysis showed that serum sortilin levels >1.66 ng/mL predicted severe CAS with sensitivity of 83.49% and specificity of 56.76%. Conclusion: Current data suggest that prediction of severe CAS may serve as an atherosclerosis biomarker and significantly contribute to research on disease progression in atherosclerosis, as well as in other arterial diseases. Sortilin may be a potential therapeutic target owing to its role in the pathogenesis of atherosclerotic carotid artery disease.